Brazil - São Paulo : Inputs for a Sustainable Competitive City Strategy, Volume 2. Background Report - World Bank (Washington, DC, 2012)
Through an analysis of selected topics, this study aims to offer inputs for a successful recovery strategy for the city and the metropolitan region of Sao Paulo (MSRP) in Brazil. The study first presents an analysis of the underlying factors of the economic transition in the MRSP, highlighting the factors behind the recent performance of the MRSP in terms of job creation and growth. Then, four inputs that would lead to a 'recovery strategy' for the MRSP are discussed in detail: The key area in the recovery strategy is 'Improving Fiscal Performance and Creditworthiness.' This is discussed in Chapter 2 and it provides an assessment of the current fiscal situation, revising the fiscal scenario, and the links between economic performance and fiscal spending. A second area of focus within the recovery strategy is 'Improving Competitiveness and the Investment Climate.' Chapter 3 assesses this issue along with the business environment in the MRSP, using both direct surveys and econometric models. A third area of focus under the MRSP recovery strategy is 'Improving Institutional Partnerships.' Chapter 4 explains this issue as confusing institutional framework; overlapping responsibilities, the lack of coordination across government levels, and little interaction with the private sector have hampered the MRSP's ability to react to economic and fiscal shocks. Finally, 'Improving Service Delivery' is the fourth focus area within the MRSP recovery strategy and is covered in chapter 5. The challenges of service delivery are illustrated in this chapter through careful examination of housing policies and programs in the Municipality of Sao Paulo.